The colonization of freed African Americans in Suriname : archival sources relating to the U.S.-Dutch negotiations, 1860-1866 - Douma, Michael J.; Douma, Michael J. (Colonial and global history through Dutch sources., 2019)
During the American Civil War, President Abraham Lincoln's administration engaged in protracted negotiations with representatives of the Netherlands to aid in the voluntarily colonization of free African Americans to Suriname. Scores of diplomatic letters in Dutch, English, and French, dating to the period 1862 to 1866 attest to the very real possibility that such migration stream could have become a reality. They also indicate reasons why this scheme failed: it was bogged down by differences of opinion, mail delays, and ultimately a reluctance of any African Americans to migrate. Previously unpublished and unknown, these letters have been transcribed and translated here for the first time. The sources provide a rare look inside the minds of liberal government officials during the age of emancipation in the Atlantic World. They demonstrate the officials' humanitarian concerns, their racial prejudices, respect for legal order and process, and faith in governments to solve international problems.